COMPARISON OF COMPLETE DENTURE FABRICATED BY TWO DIFFERENT BORDER MOLDING MATERIALS, IN TERMS OF PATIENTS' SATISFACTION - Tasleem, Robina; Saeed, Muhammad Humza Bin; Javed, Muhammad Umer (Journal of Ayub Medical College Abbottabad, 2013)
Background: Restoration of dentition leads to an improvement in the oral health related quality of life. Complete dentures are used to restore this oral cavity disability to its original condition. This study was designed to compare satisfaction levels between two groups of edentulous patients for whom two different border moulding techniques: '˜conventional green stick' and '˜polyvinyl siloxane material' were employed. Methods: This was a cross-sectional questionnaire based study. A questionnaire was designed in the Department of Prosthodontics at the Armed Forces Institute of Dentistry to compare the satisfaction levels between two groups by assessing the following four variables: '˜retention', '˜stability', '˜comfort during final impression procedure' and '˜time taken by the procedure'. Results: No significant differences were found between the two groups for '˜retention', '˜stability' and '˜comfort during the final impression procedure' (p>0.05). For '˜stability' there was a significant difference between the two groups. However, as the difference was only that of one patient (31 patients having '˜good stability' in Group A, as compared to 32 in Group B); the difference was not considered significant. The conventional border moulding technique took significantly more time as compared to the modified polyvinyl siloxane technique (p<0.05).The mean satisfaction score was low (7.36±0.45). There was a significant difference in the patient satisfaction scores between the modified and the conventional border moulding techniques (p>0.05). Conclusion: Although a significant difference was found between the patient satisfaction levels between the two groups, the clinical significance of these results is still in question as the only factor found to be different between the two groups was the '˜time taken'. Keywords: Denture, fabricated, moulding, satisfaction